Bentuk Perlindungan Hukum Bagi Wartawan Atas Tindak Kekerasan Fisik dan Non Fisik Dalam Menjalankan Tugas Profesi - Sholihuddin Anzalil Haq, Ahmad; Hufron (CV. Era Digital Nusantara, 2023)
The purpose of this study is to find out what are the forms of physical and non-physical violence against journalists in carrying out professional duties and also to find out the forms of legal protection for journalists against physical and non-physical acts of violence in carrying out professional duties such as preventive protection and efforts to overcome problems about physical violence experienced by journalists in carrying out their duties. The type used in this study is normative legal research (normative legal reaserch), and uses several approaches, namely the statutory approach (statute approach), conceptual approach (conceptual approach) and. The results of this study show the forms of violence that are often experienced by journalists Where the violence is classified as physical and non-physical violence and there are also several forms of protection of journalists in carrying out their professional duties.